2018
DOI: 10.5937/gp22-15726
|View full text |Cite
|
Sign up to set email alerts
|

Monocentric or polycentric?: Defining morphological structure of Nuts-2 regions of Turkey from 2000 to 2016

Abstract: The popularity of polycentricity has been increasing in recent years. European spatial planning literature and policy documents that emphasize the positive effects of polycentricity can be one of the reason increase in the popularity of the concept. Although not as clear and planned as in European countries, it is argued that, Turkey's metropolitan cities are also evolving from monocentric spatial structure to polycentric ones. However, there is no empirical study on the measurement of this spatial evolution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Polycentric spatial development, which is highly supported by ESDP and is becoming more popular, is the main concern of this study. Although not as clear and planned as in European countries, it is observed that, some of the metropolitan cities in Turkey are also evolving from monocentric spatial structure to polycentric ones (Sat 2018). Nevertheless, there is very limited empirical evidence on the measurement of this spatial evolution at micro-regional scale in Turkey.…”
Section: Discussionmentioning
confidence: 98%
“…Polycentric spatial development, which is highly supported by ESDP and is becoming more popular, is the main concern of this study. Although not as clear and planned as in European countries, it is observed that, some of the metropolitan cities in Turkey are also evolving from monocentric spatial structure to polycentric ones (Sat 2018). Nevertheless, there is very limited empirical evidence on the measurement of this spatial evolution at micro-regional scale in Turkey.…”
Section: Discussionmentioning
confidence: 98%
“…For the purpose of this paper we have used four analytical methods, which represent an integral part in the analysis of many researches in the field of regional geography and planning (Aydan, 2018;Đerčan et al, 2017;Filipović, 2020;Krunić, 2012aKrunić, , 2012bNevenić, 2013;Živanović et al, 2019). The aim is to use those methods which will represent Vojvodina's urban structure in the most efficient way, as well as the horizontal (spatial) and vertical (functional) hierarchy of the settlements and their interrelation.…”
Section: Methodology and Datamentioning
confidence: 99%
“…It has been applied in urban geography since the 1960s. This method provides information about the hierarchy of settlements in one administrative unit, usually based on the analysis of demographic and economic data (Aydan, 2018;Burger & Meijers, 2012;Đerčan et al, 2017;Sinclair-Smtih, 2015;Živanović et al, 2019).…”
Section: Rank-size Rule Methods and Urban Primacy Indexmentioning
confidence: 99%
See 2 more Smart Citations